Investigation of the Relationship Between Selective Voluntary Motor Control and Static Balance in Cerebral Palsy - Akalan, Ekin; Ertürk, Gamze; Evrendirek, Halenur; Karaca, Gülşah; ÖNERGE, KÜBRA (My University, 2019)
Introduction: Cerebral palsy is a group of disorders includes spasticity, contracture, balance disorder and selective motor control impairment [1], Although the relationship between selective voluntary motor control (SVMC) and gross motor function, ROM and spasticity had been investigated in literature [1], its relationship with static balance was not investigated in these children. Research Question: The aim of the study was to investigate the relationship between selective motor control and static balance in children with CP. Secondly, if there is a relationship, determining most static balance-related parameter in Selective Control Assessment of the Lower Extremity (SCALE) test. Method: Twelve children with CP (6 hemiplegics, 6 diplegic (18 legs); age: 9±3.49 y.o.) participated in the study. One-leg-standing test (OLST) and SCALE tests were used to determine static balance and motor control respectively. Duration of OLST was assessed by a stopwatch, while the participants placed both hands on hips, looked at the wall, and kept the other leg in 90° flexion. According to the duration of OLST, participants were scored between 0-3 points (0 point: could not initiate the OLST, 1 point: 0-5 sec, 2 points: 5-10 sec, 3 points: 10+ sec). Cohen correlation classification was used to define the strength of the correlation [2]. The twelve participants were above the minimum sample size needed to ensure a power of 95% confidence level. Results: A very high-level correlation was found between OLST and total SCALE score (p=0.001, r=0.75). In addition, there was a high-level correlation between OLST and ankle (p=0.023, r=0.56), subtalar joint (p=0.013, r=0.6), and toes (p=0.004, r=0.67) parameters (Table 1). Since, all participant had a full score from SCALE (Hip section) test, statistical analysis could not be performed for hip parameters. Discussion: Our study showed that static balance and SVMC have a very high to a high level relationship. In practice, physical therapists may get benefit from improving selective motor to enhance the static balance for children with CP. On the other hand, because the OLST has a high level relationship with stance phase stability during gait (ESMAC 2018), improving selective motor control in lower extremity may assist in enhancing gait quality. In the future, similar studies should be done by using dynamic balance assessments and center of pressure range calculations during walking.
Keywords: Cerebral Palsy; Selective Voluntary Motor Control; Static Balance; OLST; SCALE